IDENTIFICATION OF CHARACTERISTICS AND SUSTAINABILITY OF FISHERMAN BUSINESS IN GERAK MAKMUR VILLAGE, SAMPOLAWA DISTRICT, SOUTH BUTON DISTRICT - Herlina Herlina; Sukmawati Abdullah; Salahuddin Salahuddin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The purpose of this study is to find out now the characteristics of respondents, business sustainability and yet determine the relationship between respondents' characteristics and sustainability of fishing business in Gerak Makmur Village, Sampolawa District, South Buton Regency. The method used in this research is using quantitative analysis, with the technique of determining the sample using simple random sampling, namely random sampling, with a total sample of 42 fishermen respondents. The results of the study show that: (1) the characteristics of the respondents generally have a productive age, the education level is very low, namely elementary school, with a very experienced category, and the respondents fishermen have their own boats and fishing gear, as well as the number of dependents in the small family category; (2) the sustainability of fisherman business including capital, marketing, technology and labor belongs to the high category.